The Implementation of Discipline and Law Enforcement of Health Protocol In The District of North Banjarmasin, Indonesia - Saifudin Saifudin; Gazali Rahman; Istikhariyati Karima Gazali (International Journal of Politic, Public Policy and Environmental Issues, 2021)
This article aims to determine the implementation of government policies on applying discipline and health protocol law enforcement in the North Banjarmasin District. This study uses a qualitative approach and the type of descriptive research. Data was collected through observation, interviews, and documentation, with the Banjarmasin City Health Office, the COVID-19 Task Force, and the North Banjarmasin District as research informants. The research focuses on Van Meter and Van Horn's theory, namely, basic measures and policy objectives, policy sources, implementation activities and communication between organizations, characteristics of implementers, economic, social, and political conditions, and trends. The study results indicated that the implementation of policies on the application of discipline and law enforcement of health protocols in the District of North Banjarmasin has not yet been achieved. This can be seen from the indicators of Basic Measures and Policy Objectives that have not gone well because many still do not comply with the health protocol policy, and the officers are less strict in giving sanctions because this policy is only at the Mayoral Regulation level. Sourcespolicy this health protocol is supported by funds charged to the Banjarmasin City Budget, but infrastructure facilities are still sometimes fulfilled. Economic, Social, and Political conditions have a very negative impact on every level of society. However, judging from the indicators that the Implementation activities and Inter-Organizational Communications are appropriate, each party involved in the health protocol policy in the District of North Banjarmasin coordinates with each other. The characteristics of the implementers have a good working relationship because each activity is coordinated first, then carries out their respective duties and functions. Furthermore, the tendency of the implementers towards this health protocol policy was approved to be implemented because it has a goal that is following the current state of the COVID-19 pandemic.